The Importance of Public Participation in Sustainable Solid Waste Management - Salsabila, Lubna; Purnomo, Eko Priyo; Jovita, Hazel D. (Journal of Governance and Public Policy, 2021)
This study aims to do comparative analysis of what influence the SWM in Indonesia and the Philippines. As Sustainable Development Goals (SDGs) will not be achieved as long as the Solid Waste Management problem is left unsolved. Municipal Solid Waste Management (MSWM) has become a common issue in most developing country along with the rapid urbanization development and globalization. Qualitative approach chosen to analyze literatures selected related to SWM during 2000-2020. Data obtained from previous studies in this article were analyzed by the NVivo 12 Plus. The results shown that governance and participation become the main factors affected the status of MSWM as it is mentioned in most of the previous studies in the Philippines. Which is different with the previous studies in Indonesia.